Pollutant emissions from fossil fuel use in Kuala Lumpur and environmental damage - Lodhi, M.A.K.; Abidin, Azman Zainal; Sulaiman, M. Yusof (Elsevier, 1997)
In the Klang Valley, Malaysia, the pollutants observed include the oxides of nitrogen (NOx), ozone (O3), sulphur dioxide (SO2), carbon monoxide (CO) and suspended particulate matter (SPM). The data was collected from December 1984 to May 1989. The information presented here is based on the average hourly values obtained for the pollutants during the monitoring periods. There is a clear indication that the levels of NOx, O3 and SO2 showed a general increase through the years. However, there is no significant change in the levels of SPM and CO. The levels of all these air pollutants are, in general, below the acceptable limits set by the World Health Organization (WHO); however, the fact that they showed an increasing trend is a cause for concern when environmental damage is estimated. Copyright © 1996 Elsevier Science Ltd.